Access to single-inhaler triple medicines for chronic obstructive pulmonary disease in China: a national survey on accessibility and utilisation - Wei Li; Wei Guo; Hongdou Chen; Wei Lu; Shule Yu; Menglei Wang; Fangfang Zheng; Huanhuan Wu; Qingqing Yang (Journal of Pharmaceutical Policy and Practice)
Background The maintenance medicines for chronic obstructive pulmonary disease (COPD) include inhaled corticosteroids (ICS), long-acting muscarinic antagonists (LAMA) and long-acting β2-agonists (LABA). Budesonide/glycopyrronium/formoterol (BUD/GLY/FOR) and fluticasone furoate/umeclidinium/vilanterol (FF/UMEC/VI) are two representative drugs for prefixed ICS/LAMA/LABA association in a single inhaler and have shown comparable efficacy and safety with other ICS/LAMA/LABA open combination therapies in patients with moderate-to-very severe COPD. This study aimed to investigate the availability, price, affordability, and utilisation of single-inhaler triple medicines for COPD in China.Methods Quarterly data about the use of BUD/GLY/FOR and FF/UMEC/VI from 2020 to 2022 were collected from the Chinese Medicine Economic Information Network. We used the adjusted World Health Organization and Health Action International methodology to calculate the availability and affordability of the two investigated medicines in 596 tertiary general hospitals and 299 secondary general hospitals in 31 provincial administrative regions in China.Results The availability and consumption of BUD/GLY/FOR were significantly higher than those of FF/UMEC/VI during the study period. At the end of 2022, the availability of BUD/GLY/FOR and FF/UMEC/VI in tertiary general hospitals was 69.80% and 52.01% respectively, while in secondary general hospitals, it was 52.51% and 28.76% respectively. Both medications were equally affordable at 1.3 days of the minimum wage after reimbursement in 2022. In the first quarter of 2021, with the inclusion of both drugs in the Medicare catalog, their DDDc decreased significantly, which was accompanied by notable improvements in their availability, affordability and consumption.Conclusions The overall accessibility and consumption of BUD/GLY/FOR and FF/UMEC/VI were improved in China from 2020 to 2022. The implementation of the national drug price negotiation policy reduces the cost of drugs in China and plays an important role in improving the availability of the investigated drugs.